A METHOD OF CONTACTLESS MEASUREMENT OF SURFACE TEMPERATURE OF RADIO ELECTRONIC OBJECTS - V. K. Bityukov; A. N. Zhukov; D. S. Simachkov (Российский технологический журнал, 2016)
There exists quite an extensive bibliography on the methods of contactless measurement of temperature of the surfaces of objects. However, very few works have been devoted to studying the pyrometry of temperatures not exceeding 700 K, though these are badly needed for practical application in radio electronics, medicine, construction and other fields of science and technology. The market of modern measuring devices has plenty of domestic and foreign- made optoelectronic systems (OESs) which can be used for these purposes. However, the results obtained with the help of modern OESs in most cases need to be thoroughly analysed, for sometimes they may appear to be wrong. Most often errors occur due to unaccounted or incorrect account of spectral dependence of OES characteristics, opticophysical parameters of the object under control and its background. A procedure for the pyrometry of objects (pyrometers, thermal imagers), using OESs, is proposed, which includes planar arrangement within the view of OES of the object under investigation, the normal spectral emissivity of the surface of which is known, and a reference transmitter, the normal spectral emissivity of which is also known, and its temperature is controlled and measured. A mathematical model of the process is suggested for the mode when full heat flows of the object and the reference transmitter are equal, allowing to define the target temperature value of the object surface. Applying the method of small perturbations, a metrological analysis is made of the proposed method for determining of the temperature of the object with the use of a monochromatic OES. The method of small perturbations can be described as follows: first, based on the selected values of the parameters, using the corresponding formula, calculation is made of the value of the sought quantity. Then, the value of only one of the parameters used in the calculation is changed for the value of its measurement error, and a new calculation is made of the target value. The deviation of the obtained value from the original value characterizes the impact of inaccurate knowledge of the variable parameter on the target value. The table gives the results of calculations of wavelengths of 0.50, 2.0, 5.0, 8.0, 14 and 50 microns; of temperatures of 400, 700 and 1000 K; of normal spectral emissivity of the object of 0.1, 0.5 and 0.9; of the background temperature of 300 K; of normal spectral background emissivity of 0.5 and reference emitter of 0.98. It can be seen that a comprehensive analysis of the process of temperature measurement, the main information parameter of both the technological process of the manufacturing of objects and their thermal condition at all stages of the life-cycle, should precede both the measurement of the object surface temperature, and also the selection procedure of OES for its realization. Only obtained in this way the results can be considered reliable with the determined real measurement error.Keywords: test bench, integrated circuit chip, characteristics, algorithm, charge pump, control program, virtual panel.